Tracheal Cuff Pressure Monitoring in the ICU: A Literature Review and Survey of Current Practice in Queensland. Issue 6 (November 2014) - Talekar, C. R.; Udy, A. A.; Boots, R. J.; Lipman, J.; Cook, D.
The application of tracheal cuff pressure monitoring is likely to vary between institutions. The aim of this study was therefore to review current evidence concerning this intervention in the intensive care unit (ICU) and to appraise regional practice by performing a state-wide survey. Publications for review were identified through searches of PubMed, EMBASE and Cochrane (1977 to 2014). All studies in English relevant to critical care and with complete data were included. Survey questions were developed by small-group consensus. Public and private ICUs across Queensland were contacted, with responses obtained from a representative member of the medical or nursing staff. Existing literature suggests significant variability in tracheal cuff pressure monitoring in the ICU, particularly in the applied technique, frequency of assessment and optimal intra-cuff pressures. Twenty-nine respondents completed the survey, representing 80.5% (29/36) of ICUs in Queensland. Twenty-eight out of twenty-nine respondents reported routinely monitoring tracheal cuff function, primarily employing cuff pressure measurement (26/28). Target cuff pressures varied, with 3/26 respondents aiming for 10 to 20 cmH2 O, 10/26 for 21 to 25 cmH2 O, and 13/26 for 26 to 30 cmH2 O. Fifteen out of twenty-nine reported they had no current guideline or protocol for tracheal cuff management and only 16/29 indicated there was a dedicated area in the clinical record for reporting cuff intervention. Our results indicate that many ICUs across Queensland routinely measure tracheal cuff function, with most utilising pressure monitoring devices. Consistent with existing literature, the optimum cuff pressure remains uncertain. Most, however, considered that this should be a routine part of ICU care.